Mitigation of Acute Ammonia Emissions With Biochar During Swine Manure Agitation Before Pump-Out: Proof-of-the-Concept - Chen, Baitong; Koziel, Jacek A.; Białowiec, Andrzej; Lee, Myeongseong; Ma, Hantian; O’Brien, Samuel; Li, Peiyang; Meiirkhanuly, Zhanibek; Brown, Robert C. (Frontiers in Environmental Science, 2021)
Ammonia (NH3) emissions from animal agriculture can cause eutrophication of water ecosystems and secondary particulate matter (PM2.5). NH3 emissions from stored swine manure represent nutrient loss affecting the fertilizing value of manure. The short-term emission bursts occur when farmers agitate manure before emptying storage and fertilizing fields. There is no proven technology to mitigate gaseous emissions during agitation, while the hazards of acute releases (e.g., H2S) is are well-known. Biochar mitigates NH3 emissions from manure over the long-term. The objective of this research was to evaluate the mitigation of acute NH3 emissions during/after agitation. Two biochars, highly alkaline and porous (HAP from corn stover) and red oak (RO), were tested. 6 & 12 mm-thick layers of surficial application of biochar powder followed by 3 min agitation. NH3 concentrations were measured before/during/after agitation. Mitigation was assessed by comparing: (i) the maximum (peak) flux, (ii) total emission (from agitation start till NH3 concentration returned to the before-agitation), and (iii) the total emissions during agitation. The 12 mm HAP significantly (p<0.05) reduced (i-iii) by 63, 70, & 85%, respectively. The 6 mm HAP significantly reduced (i-iii) by 76, 75 & 78%, respectively. The 12 mm RO significantly reduced (i-iii) by 9, 53 & 57%, respectively. The 6 mm RO significantly reduced (i-iii) by 61, 86 & 63%, respectively. The NH3 emission kinetics model confirmed that a 6 mm dose was just as effective as the larger dose. More research is needed to optimize and scale-up mitigating emissions and retention of nutrients in manure with biochar.